Characterizations of global reachability of 2D structured systems - Pereira, Ricardo (2013)
The new concept of 2D structured system is deﬁned and characterizations of global reachability are obtained. This paper extends well known results for the 1D case, according to which a structured system (Aλ, Bλ) is (generically) reachable if and only if its graph is spanned by a cactus, or, equivalently, if and only if the pair (Aλ, Bλ) is full generically row rank and irreducible.